2015
DOI: 10.1007/s13213-015-1101-6
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota of the wood-feeding termite Reticulitermes lucifugus (Isoptera; Rhinotermitidae)

Abstract: Termite gut is host to a complex microbial community consisting of prokaryotes, and in some cases flagellates, responsible for the degradation of lignocellulosic material. Here we report data concerning the analysis of the gut microbiota of Reticulitermes lucifugus (Rossi), a lower termite species that lives in underground environments and is widespread in Italy, where it causes damage to wood structures of historical and artistic monuments. A 16S rRNA gene clone library revealed that the R. lucifugus gut is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…These 44 OTUs were assigned to 24 genera. We found that 12 of the 24 genera had been previously observed (Butera, Ferraro, Alonzo, Colazza, & Quatrini, ; Chou, Chen, Arun, & Young, ; Fall et al., ; Hongoh et al., ; Liu et al., ; Shinzato, Muramatsu, Matsui, & Watanabe, ; Thong‐On et al., ) but other 12 genera ( Massilia, Hydrogenophaga, Hydrogenophilus, Neisseria, Helicobacter, Thermomonas, Dokdonella, Acidiphilium, Hyphomicrobium, Paracoccus, Microvirga, and Peredibacter ) had not been reported previously for termite gut microbiota. We also found that there were eight of the 44 OTUs represented possible new taxa, as their 16S rRNA similarities to that of the currently known species were less than 97%.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…These 44 OTUs were assigned to 24 genera. We found that 12 of the 24 genera had been previously observed (Butera, Ferraro, Alonzo, Colazza, & Quatrini, ; Chou, Chen, Arun, & Young, ; Fall et al., ; Hongoh et al., ; Liu et al., ; Shinzato, Muramatsu, Matsui, & Watanabe, ; Thong‐On et al., ) but other 12 genera ( Massilia, Hydrogenophaga, Hydrogenophilus, Neisseria, Helicobacter, Thermomonas, Dokdonella, Acidiphilium, Hyphomicrobium, Paracoccus, Microvirga, and Peredibacter ) had not been reported previously for termite gut microbiota. We also found that there were eight of the 44 OTUs represented possible new taxa, as their 16S rRNA similarities to that of the currently known species were less than 97%.…”
Section: Resultssupporting
confidence: 58%
“…We successfully cultivated a range of bacterial strains belonging to the Delftia, Comamonas, Acinetobacter, Moraxella, Luteimona, Sphingomonas, Bosea, Methylobacterium, Corynebacterium, Janibacter, Propionibacterium, and Sphingobacterium with MSP method in this study. Of note, the occurrence of these bacterial taxa in termite gut had been previously detected with molecular tools but they had not been cultivated (Butera et al, 2016;Diouf et al, 2015;Fall et al, 2007;Hongoh et al, 2005;Husseneder, Berestecky, & Grace, 2009;Matsui, Tanaka, Namihira, & Shinzato, 2012;Nakajima, Hongoh, Usami, Kudo, & Ohkuma, 2005;Thong-On et al, 2012;Visser, Nobre, Currie, Aanen, & Poulsen, 2012;Zhu et al, 2012). The members of Massilia, Hydrogenophaga, Hydrogenophilus, Neisseria, Helicobacter, Thermomonas, Dokdonella, Acidiphilium, Hyphomicrobium, Paracoccus, Microvirga, Peredibacter, Anaerococcus, Aneurinibacillus, Geobacillus, Gemella, Alicyclobacillus, Veillonella, Oribacterium, Faecalibacterium, Prevotella, Alloprevotella, Flavisolibacter, and Flavobacterium represented an unclassified member of Proteobacteria, and its 16S…”
Section: Discussionmentioning
confidence: 99%
“…This study allowed to unveil the role of some prokaryotes located in the hind gut of the subterranean termite P. hypostoma and confirm their principle role in cellulose digestion and nutrition. Another important role of the aerobic cellulolytic bacteria in the termite gut may be the consumption of oxygen and the creation of appropriate anaerobic conditions for the symbiotic obligatory anaerobic microorganisms (protozoa) that are indispensable for the digestion of consumed cellulose by the termites (Brune et al 1995; Brune 1998; Butera et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…From each region, five guts of healthy adult isopods were extracted with fine-tipped sterile forceps (Butera et al 2016), pooled and homogenized to be serially diluted in a sterile physiological solution and plated on Nutrient Agar (NA; Difco, Franklin Lakes, NJ) culture medium. After 72 h of incubation at 37°C, the colonies were counted and the mean number of bacteria per gut was determined.…”
Section: Bacterial Counts and Isolation From The Digestive Tissuesmentioning
confidence: 99%
“…Adult isopods (both males and females) were surfacesterilized with 70% ethanol, washed twice with distilled water and surface dried; their guts were dissected and used freshly for DNA extraction (Butera et al 2016). From each population, five pooled guts were used for total DNA extraction and purification using the QIAamp® DNA Stool Kit (QIAGEN, Venlo, The Netherlands) according to the manufacturer's instructions.…”
Section: Dna Extraction From Digestive Tissuesmentioning
confidence: 99%